1974
DOI: 10.1111/j.1365-2672.1974.tb00486.x
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Bacillus Spores to Combined Sporicidal Treatments

Abstract: Summary. Moist heat at 82° (100° for Bacillus stearothermophilus) and solutions of 0.2% w/v chlorocresol or 0.01% w/v benzalkonium chloride at 24° separately showed no sporicidal activity against B. pumilis, B. stearothermophilus, B. subtilis and B. subtilis var. niger. Spores of the last organism were the most sensitive to γ radiation, the D value being 0.16 Mrad. Prior irradiation with a dose of 0.16 Mrad brought about only a slight increase in the sensitivity of the spores to moist heat. The presence of ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

1976
1976
1997
1997

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 13 publications
(4 reference statements)
0
7
0
Order By: Relevance
“…In contrast, concentrations as low as 0.2% (phenol), 0.08% (cresol), and 0.02% (chlorocresol) (wt/vol) are all effective inhibitors of germination (173). Furthermore, sporicidal activity is greatly accelerated when phenolics are used at elevated temperatures (33). Such a process, utilizing 0.2% (wt/vol) chlorocresol at 98 to 100'C, was for many years a pharmacopoeial process in the United Kingdom for sterilizing certain injectable and ophthalmic products, but is no longer official.…”
Section: Sporostatic and Sporicidal Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, concentrations as low as 0.2% (phenol), 0.08% (cresol), and 0.02% (chlorocresol) (wt/vol) are all effective inhibitors of germination (173). Furthermore, sporicidal activity is greatly accelerated when phenolics are used at elevated temperatures (33). Such a process, utilizing 0.2% (wt/vol) chlorocresol at 98 to 100'C, was for many years a pharmacopoeial process in the United Kingdom for sterilizing certain injectable and ophthalmic products, but is no longer official.…”
Section: Sporostatic and Sporicidal Activitymentioning
confidence: 99%
“…These involve a combination of a chemical and a physical process or of two chemical agents (1 The bactericidal and sporicidal activity of a biocide increases with increasing temperature. For example, the temperature coefficient (0) per 1C rise in temperature for the phenolic agent chlorocresol is 1.1 (33). If the temperature is increased from 20 to 1000C, then assuming that 0 is the same over the entire temperature range, the activity increases by >2,000-fold (0100-20 = 1.180 = 2,104).…”
Section: Outgrowthmentioning
confidence: 99%
“…At the concentrations used and for the times recommended, aldehyde fixatives may be considered to be sporicidal and thus effective as tissue sterilants. 18 When various mixtures of alcohol and polyethylene glycol (PEG) are used as fixatives, for example Kryofix or Spuitfix, the fixation of tissue is excellent; however, the sterilising effects on clinical material so fixed have not been investigated. It is known that 70% wt/vol alcohol will kill many Gram positive and Gram negative bacteria, some viruses, and some fungi, justifying its use as an effective antiseptic and disinfecting medium in many applications.…”
mentioning
confidence: 99%
“…6 ) that cysteine could replace thioglycollate in such media. Thioglycollate does not always enhance the recovery of bacteria exposed to a mercury compound ;Briggs & Yazdany (1974) have shown that spores of bacilli treated with phenylmercuric nitrate gave similar counts on Antibiotic Assay Medium with or without thioglycollic acid. In a study with merthiolate, Price (1950) reported that simple dilution was far less effective than a chemical inactivator in reversing the activity of the disinfectant.…”
Section: Mercury Compoundsmentioning
confidence: 99%